Kondisi Sosial Kehidupan Pemulung di Kota Makassar - Ardi M. Yusuf (Siddiq Institute, 2023)
this studi aims to determine the socio economic conditions between scavengers who operate in the landfill, which shows that the social and economic life of the scavenger community is still vulnerable to poverty, while the results of scavengers in the TPA have not been able to neutralize the needs of life. From the sale of used goods, carboard aqua bottles and so on. Socially people who work scavengers are people who come from groups who are very have to be at the disposal site every day. To collect every day used goods that they can use as rupiah to make a living.